Assessing secondary level students' critical thinking skills: inspiring environmental education for achieving sustainable development goals. (June 2020) - Uddin, M R; Shimizu, K; Widiyatmoko, A
Abstract: The study intends to measure secondary level students' critical thinking skills. This study follows a survey method and is a part of a doctoral dissertation focusing on promoting critical thinking skills of environmental education for achieving sustainable development goals (SDGs). The data were collected by using the Critical Thinking Skills test on Environmental Education (CTSEE) comprises of 27 items. The participants were the 8 th grade students (N=444) from 13 secondary schools that cover four administrative districts of Bangladesh. The Instrument was adopted from previous research that consists of three aspects (Conclusion, Inference, and Identifying Bias) of critical thinking skills. The result shows that the students' critical thinking skills on environmental issues can be categorized into the poor and very poor category, and there are statistically significant differences between male and female students. The study will be used as the reference for developing students' critical thinking skills about the surrounding environment-related problem in line with achieving the globally decided environmental sustainability as well as sustainable development goals.